Glucose lowering and vascular protective effects of cycloset added to GLP‐1 receptor agonists in patients with type 2 diabetes - Alatrach, Mariam (Endocrinol Diabetes Metab, 2018)
OBJECTIVE: To determine the glucose‐lowering mechanism of action and the effects of a quick‐release bromocriptine‐QR, a D2‐dopamine agonist (Cycloset) on vascular function in patients with type 2 diabetes (T2D). STUDY DESIGN AND METHODS: Fifteen poorly controlled T2D treated with metformin plus glucagon‐like peptide‐1 receptor agonists (GLP‐1RA) were studied after 4 months of Cycloset, 3.2 mg/d. Subjects received a 5‐hour double‐tracer (iv 3‐(3)H‐glucose and oral (14)C‐glucose) mixed meal test (MMT) to quantitate rates of endogenous glucose production (EGP), oral glucose appearance (RaO) and disappearance (Rd) pre‐ and post‐Cycloset. Vascular assessments included 2‐day continuous BP monitoring, reactive hyperaemia index (RHI) and arterial stiffness (AS). RESULTS: HbA(1c) decreased from 8.3 ± 0.3% to 7.7 ± 0.2% (P < 0.05), fasting plasma glucose did not change (143 ± 4 vs 147 ± 5) and mean plasma glucose during MTT decreased from 223 ± 3 to 210 ± 4 mg/dL (P < 0.05) after Cycloset. Basal EGP (2.2 ± 0.2 vs 2.1 ± 0.2 mg/kg min) was unchanged, but there was greater MMT suppression (1.1 ± 0.1 vs 0.7 ± 0.1, P < 0.05). After Cycloset, RaO declined from 2.0 ± 0.1 to 1.7 ± 0.2 mg/kg min and peripheral oral glucose appearance from 53.1 ± 3.2 to 44.4 ± 3.1 g (P < 0.01). There were no changes in plasma insulin or glucagon concentration. Systolic (134 ± 4 vs 126 ± 6), diastolic (78 ± 3 vs 73 ± 4), mean BP (97 ± 5 vs 90 ± 4) and pulse pressure (54 ± 2 vs 51 ± 2 mm Hg) were reduced; RHI increased from 1.4 ± 0.1 to 1.9 ± 0.3 au and AS decreased modestly (19.8 ± 4.1 to 16.2 ± 3.7 au, P = NS). CONCLUSIONS: Addition of Cycloset to GLP‐1 RA improved vascular indices and postprandial hyperglycaemia in T2DM primarily by lowering oral glucose appearance, suggesting that hepatic glucose uptake was enhanced. Improved vascular indices may explain the reduction in cardiovascular events observed with Cycloset therapy in patients with T2DM.